DAMPAK PENGEMBANGAN PARIWISATA TERHADAP KESEJAHTERAAN MASYARAKAT (Studi Kasus Pada Masyarakat Pelaku Usaha di Sekitar Objek Wisata Pantai Selong Belanak, Kecamatan. Praya Barat, Kabupaten. Lombok Tengah) - RUSLAN JAYADI (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2024)
Selong Belanak is a village located in the southern part of Central Lombok Regency and is in West Nusa Tenggara Province which has a lot of marine tourism potential. Seeing the existing potential, local governments and communities have made various tourism development efforts consisting of tourist attractions, promotion or marketing, tourist markets, transportation, as well as tourist facilities and services to increase the number of tourists. This research aims to find out whether the development of Selong Belanak Beach tourism has an impact on the welfare of the community around the tourist attraction. This research is descriptive qualitative in nature. The data sources used are primary data and secondary data. By using data collection methods, namely interviews and documentation. The research results show that the components of tourism development consist of tourist attractions, promotion or marketing, transportation tourism markets and tourist facilities and services. The development of Selong Belanak Beach tourism has an impact on the welfare of the people of Selong Belanak Village who are around the tourist attraction. The significant impact felt by the people of Selong Belanak is the opening of business opportunities, these business opportunities consist of culinary businesses, accommodation businesses, laundry businesses, surfing, shops, grocery stores, motorbike rental services and guide rental services